Valuable rubidium extraction from potassium reduced seawater brine. (10th February 2018) - Naidu, Gayathri; Jeong, Sanghyun; Choi, Youngkwon; Song, Min Hyung; Oyunchuluun, Undram; Vigneswaran, Saravanamuthu
Abstract: Extraction of rubidium (Rb) which is an economically valuable metal from seawater reverse osmosis (SWRO) brine is beneficial. However, potassium (K) in SWRO brine hinders Rb extraction. Natural clinoptilolite zeolite in powder form was able to selectively remove K from SWRO brine (Langmuir maximum sorption, Qmax (cal.) = 57.47 ± 0.09 mg/g). An integrated submerged membrane sorption reactor (SMSR) containing zeolite powder achieved 65% K removal from SWRO brine. Periodic replacement of zeolite in SMSR, coupled with membrane backwashing was effective in maintaining a high K removal efficiency and a stable transmembrane pressure. Less than 5% Rb losses occurred along with K sorption, establishing the high K selectivity by zeolite in SWRO brine. Utilization of K loaded zeolite as a slow release fertilizer would be beneficial for agriculture. In SWRO brine with reduced K contents, the Rb sorption efficiency of polymer encapsulated potassium copper hexacyanoferrate (KCuFC(PAN)) sorbent, increased significantly from 18% to 83%. Graphical abstract: Image 1